2011
DOI: 10.1590/s1516-44462011000500005
|View full text |Cite
|
Sign up to set email alerts
|

Estudos latino-americanos sobre melancolia: um transtorno do humor melhor definido para o CID-11

Abstract: ResumoObjetivo: A depressão melancólica é um diagnóstico psiquiátrico de história de vida, geralmente com episódios recorrentes. Melancolia é uma síndrome com longa duração e características específicas de psicopatologia, insuficientemente diferenciada de depressão maior por um especificador no DSM-IV e parcialmente descrito nos critérios da Classificação Internacional de Doenças-10ª Edição. Dentro da classificação atual, é frequentemente vista em pacientes gravemente doentes com depressão e transtorno bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…From the literature search on endocrine factors, a particular study demonstrated varied HPA axis function depending on severity of depression in humans [12]. Nandam et al demonstrated that the rate of the secretion of a specific hormone was altered in human patients with MDD [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature search on endocrine factors, a particular study demonstrated varied HPA axis function depending on severity of depression in humans [12]. Nandam et al demonstrated that the rate of the secretion of a specific hormone was altered in human patients with MDD [13].…”
Section: Resultsmentioning
confidence: 99%
“…The endocrine hypothesis displays a relation between the impacts of stress and the pathogenesis of MDD, through analysis of the HPA axis. This is because the HPA axis is one of the most important components in regulating homeostasis in response to stress [21]. Figure 1 displays the mechanism by which the HPA axis responds to stress.…”
Section: Endocrinementioning
confidence: 99%